Racial disparities in the Paycheck Protection Program - Chernenko, Sergey; Scharfstein, David (Journal of Financial Economics, 2024)
Consistent with contemporaneous research, we document that minority-owned firms were more likely than observationally similar white-owned firms to receive PPP loans from nonbank lenders than from banks. However, we show that this substitution to nonbanks was only partial, resulting in significantly lower PPP take-up by minority-owned firms, particularly Black-owned ones. Location and firm characteristics explain about two-thirds of the 25 percentage point disparity in PPP take-up by Black-owned firms. While there was greater substitution to nonbanks in more racially biased locations, overall take-up was still lower in those locations. Access to professional help with applications facilitated use of nonbanks and mitigated disparities.